Investigation on microstructure and properties of TiCx-graphite/Cu composites fabricated by a novel in-situ reactive synthesis. (February 2023) - Wei, Hongming; Li, Zhiqiang; Zou, Jianpeng; Gong, Yurong; Li, Xiaoya; Zhan, Wenyi; Li, Feiyang; Dai, Yanzhang
Abstract: TiCx -graphite/Cu composites were prepared by spark plasma sintering using copper-coated graphite powder, copper powder, and Ti2 SnC powder as raw materials. The phase composition, microstructure, relative density, hardness, and conductivity of the composites prepared with 25, 30, 35, and 40 wt% Ti2 SnC were studied in this paper. The results show that TiCx would be synthesized from Ti2 SnC in situ during the sintering process, and Sn atoms diffused out from Ti2 SnC and into the Cu matrix. The relative density and of hardness the composites prepared with different Ti2 SnC content was above 93% and 65 HSD, respectively. The conductivity of the composites decreased from 1.696 × 10 7  S m −1 to 9.380 × 10 6  S m −1 with the Ti2 SnC content increasing from 25 to 40 wt%. Graphical abstract: Image 1 Highlights: TiCx -graphite/Cu composites were prepared with copper-coated graphite, copper and Ti2 SnC. TiCx was synthesized from Ti2 SnC in situ. The microstructure and properties of TiCx -graphite/Cu composites were investigated. The composites samples were analyzed by XRD, SEM and EDS.